2014
DOI: 10.1007/s13105-014-0330-7
|View full text |Cite
|
Sign up to set email alerts
|

Serum IL-10 involved in morphine tolerance development during adjuvant-induced arthritis

Abstract: Opioid receptors play an important role in modulation of hyperalgesia in inflamed tissues, but chronic morphine application induces such side effects as tolerance. There is near communications between cytokines and mu opioid receptor expression. This study was aimed to assess the role of serum IL-10 in morphine tolerance development during adjuvant-induced arthritis. Adjuvant arthritis (AA) was induced on day 0 by single injection of Complete Freund's Adjuvant (CFA) into the rats' hindpaw. Hyperalgesia, edema,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
1
7
1
Order By: Relevance
“…Inflammation was induced on the day 0 by a single sub-cutaneous injection of 100 μL CFA into the right hindpaw (Zaringhalam et al, 2014). This animal model indicates a rapid primary inflammation response to the adjuvant (Santora, Rasa, Visco, Steinetz, & Bagnell, 2007).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammation was induced on the day 0 by a single sub-cutaneous injection of 100 μL CFA into the right hindpaw (Zaringhalam et al, 2014). This animal model indicates a rapid primary inflammation response to the adjuvant (Santora, Rasa, Visco, Steinetz, & Bagnell, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…The edema was quantified by measuring the paw volume differences between the day zero and other time points of the study. The paw volumes were shown as the percentage of the day zero (Zaringhalam et al, 2014). …”
Section: Methodsmentioning
confidence: 99%
“…Finally, the blots were visualized with a chemiluminescence detection system (ECL, Amersham, RPN2235). Band intensity was measured densitometrically using Image J and expressed as the ratio of the intensity of the BDNF, pro-BDNF, Iba1, and Caspase-3 band to β-actin [36].…”
Section: Western Blotmentioning
confidence: 99%
“…As a potent immune-regulatory cytokine, IL-10 exhibits critical impact on modulating inflammation and directing adaptive immune response [98]. Spinal MOR, which has been proved to be involved in the development of morphine tolerance, is related to the regulation of serum anti-inflammatory cytokine IL-10 in adjuvant arthritis (AA) morphine-tolerant rats [99]. The expressions of spinal MOR and serum IL-10 were both increased in AA morphine-tolerant rats.…”
Section: Anti-inflammatory Cytokines and Morphine Tolerancementioning
confidence: 99%
“…The development of morphine tolerance in AA rats occurred markedly later than control group. Additionally, daily administration of anti-IL-10 antibody could significantly enhance the thermal hyperalgesia, decrease the spinal MOR expression and accelerate the development of morphine tolerance in AA rats [99]. These results suggested that the up-regulation of serum IL-10 might inhibit the development of morphine tolerance via modulating spinal MOR expression in AA rats.…”
Section: Anti-inflammatory Cytokines and Morphine Tolerancementioning
confidence: 99%